UTILIZATION OF COVID-19 DIGITAL MEDIA LITERACY THROUGH THE NEW HABIT MARBLE ONLINE GAME IN EARLY CHILDREN - Kurniawati, Laurencia Steffanie Mega Wijaya; Marta, Rustono Farady; Amanda, Mercedes (Journal Communication Spectrum: Capturing New Perspectives in Communication, 2020)
Abstract The rapidly developing communication and information technology has forced government agencies to adapt by disseminating information or educating the public through digital media. MARBEL online games with the theme of new habits provide a means of disseminating education related to the importance of maintaining a clean and healthy body, especially for early childhood. This study aims to analyze the content of the game using Philip Mayring's qualitative content analysis method regarding categorized interpretations based on characteristics in a reality, which in this study is a game for early childhood MARBEL New Habits. This is in line with government policies and efforts to harmonize community activities in the new normal era. In addition, it is also supported by the optimization of the use of Digital Media Literacy as a theoretical framework that is presented to understand the importance of technological advances in the midst of the COVID-19 Pandemic, this conceptual dimension that is comprehensively discussed also functions as a cognitive construction tool for early childhood related to a new hygiene culture known as a protocol. health. The results of this study show that the ability to play online which is close to the child's environment can have a significant positive effect, especially on new habits of early childhood, as well as show that technological advances provide opportunities for policymakers to disseminate information and education to the community. Keywords: Content Analysis, Mayring, MARBEL Online Game, COVID-19, Digital Media Literacy. Abstrak Teknologi komunikasi dan informasi yang berkembang pesat membuat lembaga pemerintah harus ikut beradaptasi dengan melakukan penyebaran informasi ataupun edukasi masyarakat melalui media digital. Permainan daring MARBEL dengan tema kebiasaan baru memberikan sarana dalam penyebaran edukasi terkait pentingnya menjaga kebersihan dan kesehatan tubuh khususnya bagi anak usia dini. Penelitian ini bertujuan menganalisis konten permainan tersebut menggunakan metode analisis isi kualitatif Philip Mayring mengenai interpretasi yang dikategorisasikan berdasarkan karakteristik dalam sebuah realitas, yang dalam penelitian ini adalah permainan bagi anak usia dini MARBEL Kebiasaan Baru. Hal ini sejalan dengan kebijakan dan upaya pemerintah guna menyelaraskan aktivitas masyarakat dapat berlangsung dengan baik di era new normal. Selain itu juga ditunjang optimalisasi penggunaan Literasi Media Digital sebagai rerangka teoritis yang dihadirkan untuk memahami pentingnya kemajuan teknologi di tengah Pandemik COVID-19, dimensi konsptual yang dibahas secara komprenhensif ini difungsikan pula sebagai alat konstruksi kognitif anak usia dini terkait budaya kebersihan baru yang dikenal sebagai protokol kesehatan. Hasil dari penelitian ini memperlihatkan kemampuan permainan daring yang berada dekat pada lingkungan anak dapat memberikan pengaruh positif khususnya pada kebiasaan baru anak usia dini secara signifikan sekaligus memperlihatkan bahwa kemajuan teknologi memberikan peluang bagi pemangku kebijakan dalam penyebaran informasi maupun edukasi kepada masyarakat. Kata kunci: Analisis Konten, Mayring, MARBEL, COVID-19, Literasi Media Digital. To cite this article (7th APA style):Kurniawati, L. S. M. W., Marta, R. F. & Amanda, M. (2020). Utilization of Covid-19 Digital Media Literacy through the New Habit Marble Online Game in Early Children. Journal Communication Spectrum: Capturing New Perspectives in Communication, 10(2), 105-115. http://dx.doi.org/10.36782/jcs.v10i2.2142